The Application of “The Jungle Book” Theme in the Interior Design of Manimonki Animation Studio in Surakarta - Akbar, Muhammad Fakhrezi; Studyanto , Anung B. (Pendhapa, 2023)
Indonesia is one of the countries with the highest popularity of animation in the world. However, the city of Surakarta lacks facilities to develop and support the potential of animation film-making communities. The lack of attention from the local government as a facilitator and enabler poses a problem, leading these communities to prefer working in larger cities with national-scale studios, thereby risking Surakarta's market segment in animation. This study aims to design the interior of Manimonki Animation Studio in Surakarta to provide a facility that can accommodate and support the local animation film-making community, enhancing the growth of the animation industry in Indonesia to compete internationally. The interior design of this studio adopts a unique theme, "Jungle Book," inspired by the 1967 American musical comedy animated film produced by Walt Disney Productions. The theme serves as a foundational concept for designers to address and solve design problems encountered. The methodology includes literature studies, field studies, and interviews to gather data, followed by zoning, grouping, and space organization to structure the interior design. The results indicate that the Jungle Book theme creates a creative and engaging work environment, boosting productivity and minimizing fatigue.